A new seismic damage assessment method for single-layer steel latticed shells considering multi-modal contribution. (October 2021) - Zhang, Yujian; Luo, Yongfeng; Guo, Xiaonong; Li, Yunsong; Huang, Qinglong
Abstract: In this paper, a new seismic damage assessment method considering multi-modal contribution is proposed to evaluate the seismic damage of single-layer steel latticed shells more accurately and efficiently. In the proposed method, the contribution of each modal damage to the structural overall seismic damage is calculated based on a specially constructed equivalent static system derived in this paper, in which the structural multi-modal damage effects can be considered. Then, the measure technics of the structural seismic damage degree is proposed in this paper according to the equivalent static displacements, and then the recommended damage index equation is derived. Considering different actual engineering requirements, the damage assessment procedures for design and appraisal are given in this paper, respectively. Since the damage assessment process is based on the static analysis results of equivalent model, the proposed method retains the conceptual simplicity and computational attractiveness. For detailed comparative evaluation, several numerical examples carried out on a Kiewitt-6 single-layer latticed shell and a practical engineering structure, named Shanghai International Convention Centre, are conducted in this paper. In numerical examples, the influence of the damage assessment direction on the assessment results, the trend characteristic of damage index curves and its comparison with structural response are all discussed in detail. For practicality, combined with the numerical analysis results, seismic damage grades of single-layer latticed shells and the recommended values of characteristic points are discussed and obtained. Furthermore, seismic damage assessment results generated by the proposed method and the other three methods are compared, which confirms the necessity of considering multi-modal contribution and the satisfying accuracy and applicability provided by the proposed method in single-layer steel latticed shell seismic damage assessment.